2019
DOI: 10.1111/trf.15219
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the antiplatelet effect of ticagrelor by simulated platelet transfusion

Abstract: BACKGROUND Reversal of antiplatelet therapy is desirable in patients presenting with life‐threatening bleeding or requiring urgent surgery. This study aimed to examine ticagrelor reversal using donor platelets and to explore the effects of residual ticagrelor on donor platelets. STUDY DESIGN AND METHODS In Cohort 1, 16 healthy subjects were treated with ticagrelor 90 mg twice daily alone or in combination with aspirin 100 mg once daily for 7 days followed by single blood sampling for preparation of platelet‐ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The mechanisms of T-PPP on the efficacy of PM-r-SAK need to be further elucidated. In our previous study, we found that ticagrelor-treated plasma could significantly inhibit the aggregation of donor platelets . As ticagrelor is not a prodrug and does not require metabolic activation for antiplatelet activity, the plasma parent ticagrelor can directly inhibit the aggregation of the donor platelets .…”
Section: Resultsmentioning
confidence: 93%
“…The mechanisms of T-PPP on the efficacy of PM-r-SAK need to be further elucidated. In our previous study, we found that ticagrelor-treated plasma could significantly inhibit the aggregation of donor platelets . As ticagrelor is not a prodrug and does not require metabolic activation for antiplatelet activity, the plasma parent ticagrelor can directly inhibit the aggregation of the donor platelets .…”
Section: Resultsmentioning
confidence: 93%
“…Given a number of recent clinical studies (Godier et al, 2015;Trenk et al, 2019;Willeman et al, 2018;Zhang et al, 2019) we sought to probe the reversibility of ticagrelor binding to the P2Y12R in comparison with other receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies indicate that platelet supplementation via transfusion does not rescue platelet inhibition resulting from ticagrelor action (Godier et al, 2015;Trenk et al, 2019;Willeman et al, 2018;Zhang et al, 2019). Potentially this is because ticagrelor and its active metabolite (AR-C124910XX) have much longer half-lives ( 9and 12 hrs, respectively) than the thienopyridine derivatives prasugrel and ticagrelor with their ongoing presence able to inhibit fresh platelets at the time of the transfusion (Butler & Teng, 2010;Cave et al, 2019;Zhu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a model, aspirin‐treated platelets can be mixed with untreated platelets. The addition of 10% to 60% v/v untreated platelets to aspirin‐inhibited platelets in vitro ameliorates aspirin‐mediated inhibition of ADP and AA‐induced aggregation, as only a fraction of the total platelet population must be replaced to restore full COX‐1 activity. This is of importance for transfused platelets, as they could affect the recipient’s COX‐1 activity if the donor had taken aspirin prior to donation.…”
Section: Nsaids and Implications For Transfusion Of Platelet Productsmentioning
confidence: 98%